2003
DOI: 10.1179/096797803225009210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water absorption on frost resistance of clay roofing tiles

Abstract: clay was also applied as an admixture. In addition, the Vuppor organic admixture 6 was used to modify the pore H igh f rost resistance is one of the signs of good quality structure of test specimens. in clay roo ng tile products. T he present paper deals with the question of whether the water absorption of clay roo ng tiles aVects f rost resistance. T he results PREPARATION OF SPECIMENSshow that clay roo ng tiles with high water absorption Mineral admixtures were added to the brick clay in doses can be just as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 0 publications
3
15
0
Order By: Relevance
“…For all freezing temperatures, the density increased with temperature up to 1100 • C, but it dropped above 1100 • C. On the other hand, both porosity and water absorption decreased monotonically up to 1100 • C, but these rose for the freezing temperatures of −10 and −30 • C and dropped for room temperature and the freezing temperature of −50 above 1100 • C. It is reported that there is a correlation between pore distribution and frost resistance. [2][3][4][5][6]16 was measured by the mercury intrusion method. The results are plotted with the diameter of pore as abscissa against pore volume per unit weight, which was calculated from the data of accumulated pore-size distribution, as ordinate.…”
Section: Dependences Of Fracture Stress and Fracture Toughness On Firmentioning
confidence: 99%
See 2 more Smart Citations
“…For all freezing temperatures, the density increased with temperature up to 1100 • C, but it dropped above 1100 • C. On the other hand, both porosity and water absorption decreased monotonically up to 1100 • C, but these rose for the freezing temperatures of −10 and −30 • C and dropped for room temperature and the freezing temperature of −50 above 1100 • C. It is reported that there is a correlation between pore distribution and frost resistance. [2][3][4][5][6]16 was measured by the mercury intrusion method. The results are plotted with the diameter of pore as abscissa against pore volume per unit weight, which was calculated from the data of accumulated pore-size distribution, as ordinate.…”
Section: Dependences Of Fracture Stress and Fracture Toughness On Firmentioning
confidence: 99%
“…But, when they are used in cold districts, frost damage which is caused by the freezing of water which has permeated into the numerous pores existing in that material become a serious problem. [1][2][3][4] To describe in details, when water contained in some of these pores following rainfall freezes into ice due to a decrease of temperature, local high tensile stress will arise around these pores, and micro-cracks will be generated. These micro-cracks will grow and join with each other until the final fracture occurs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this parameter, a principle applies, that if its value grows, the frost resistance also increases. 23) Frost resistance value can be, however, affected by properties of the input material and the firing temperature. If the input material contains substances whose presence radically increases the volume of pores in the brick body then an increase of frost resistance is significantly slowed.…”
Section: )mentioning
confidence: 99%
“…The literature, 23) for example states the knowledge about the influence of pore volume on the frost resistance of a brick body. Here it was found that at almost the same water absorption or the same pore volume in the brick body, the author obtained different frost resistance values.…”
Section: Inroductionmentioning
confidence: 99%